Suppose that g(X)=f(cx). Show from the definition that g'(x)=cf'(cx)

Similar Questions
  1. Use the limit definition of the derivative to find f′(x) if1. f(x) = x^2 + 3x 2. f(x) = 1/x + 1 now what i am confuse with is
    1. answers icon 2 answers
  2. Suppose the functiona) Use the definition of the derivative to show that f ' (-2) = -1. b) Write an equation for the line
    1. answers icon 0 answers
  3. Suppose the function f(x)=4/xa) Use the definition of the derivative to show that f ' (-2) = -1. b) Write an equation for the
    1. answers icon 2 answers
  4. adage definitionCitadel definition decree definition discordant definition evolved definition hovered definition precludes
    1. answers icon 3 answers
more similar questions